PAPILLON-LEFÃˆVRE SYNDROME - Javeria, Javeria; Samiullah, Samiullah; Neelofar, Neelofar; Maryam, Maryam (Journal of Ayub Medical College Abbottabad, 2005)
A 9 years old male presented with keratotic plaques over the skin of his palms and soles extending onto the dorsal surface and swollen gums since the age of 4 with subsequent loss of most of his permanent dentition. These findings are consistent with Papillon-LefÃ¨vre syndrome. Key words: Papillon-Lefevre syndrome (PLS), palmar-plantar keratoderma, periodontitis, premature teeth loss